The 6-girth-thickness of the complete graph - Héctor Castañeda-López; Pablo C. Palomino; Andrea B. Ramos-Tort; Christian Rubio-Montiel; Claudia Silva-Ruiz (AKCE International Journal of Graphs and Combinatorics, 2020)
The g-girth-thickness of a graph G is the minimum number of planar subgraphs of girth at least g whose union is G. In this paper, we determine the 6-girth-thickness of the complete graph Kn in almost all cases. And also, we calculate by computer the missing value of